A hierarchical theory of occupational segregation and wage discrimination. - Baldwin, Marjorie L.; Butler, Richard J.; Johnson, William G. (Economic Inquiry, 2001)
Becker's model of discrimination is extended to the case where men exhibit distastes for working under female managers. The distribution of women in the resulting occupational hierarchy depends on the number of women in lower occupations, the wages of male workers in lower occupations, and male distastes for female management. Thus, there exists an occupational sorting function, related to wages, that determines the occupational distribution of women. We integrate this sorting function into a standard wage equation to derive a new decomposition of male-female wage differentials and apply it to a sample of insurance industry workers from the 1988 CPS. (JEL J71) Reprinted by permission of the publisher.